First record of Trypanosoma sp. (Protozoa: Kinetoplastida) in tuvira (Gymnotus aff. inaequilabiatus) in the Pantanal wetland, Mato Grosso do Sul State, Brazil - Pádua, Santiago Benites de [UNESP]; Ishikawa, Márcia Mayumi; Satake, Fabiana; Jerônimo, Gabriela Tomas; Pilarski, Fabiana [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2011)
O objetivo do presente estudo foi reportar a infecção por Trypanosoma sp. em tuviras (Gymnotus aff. inaequilabiatus) oriundas do Pantanal Sul-mato-grossense, Brasil. Dez peixes provenientes do rio Paraguai, Pantanal Sul-mato-grossense, foram avaliados quanto à presença de hemoflagelados. Tripomastigotas de Trypanosoma sp. foram observados nas extensões sanguíneas de três peixes (30% de prevalência), e algumas formas encontravam-se em divisão. Por meio do exame a fresco e da centrifugação do sangue em capilar de hematócrito como métodos para diagnóstico, a taxa de prevalência foi de 80%. Esse é o primeiro relato de Trypanosoma sp. em tuviras no Brasil.

The blood infection by Trypanosoma sp. in tuvira (Gymnotus aff. inaequilabiatus) from the Pantanal wetland was reported in this study. Ten fish from the Paraguay River in the Pantanal were evaluated for the presence of hemoflagellates. Trypomastigotes of Trypanosoma sp. were observed in blood smears from three fish (30% prevalence) and some forms were seen to be undergoing division. Using the diagnostic methods of fresh examination and blood centrifugation in hematocrit capillary tubes, the prevalence rate was 80%. This is the first report of Trypanosoma sp. in tuvira in Brazil.
Primeiro registro de Trypanosoma sp. (Protozoa: Kinetoplastida) em tuvira (Gymnotus aff. inaequilabiatus) no Pantanal, Mato Grosso do Sul, Brasil
Keywords: Hemoflagelado; hemoprotozoário; isca viva; Hemoflagellate; hemoprotozoa; live bait